ANALISIS PERTIMBANGAN HUKUM PENGADILAN AGAMA PENETAPAN NOMOR 92/Pdt.P/2023/PA.Ptk TENTANG PERMOHONAN ASAL USUL ANAK - NIM. A1011191321, SYARIFAH FAIRUS (Jurnal Fatwa Hukum, 2025)
Abstract  . The application for the origin of the child was granted by the Religious Court based on Article 42 and Article 2 paragraph 1 of Law Number 1 of 1974, which states that a legitimate child is a child born from a valid marriage according to religious law. As long as the applicant can prove the existence of a valid marriage, the child will be recognized as a legitimate child with full legal status. However, if the marriage cannot be proven, the application is still granted, but the child is only recognized as a biological child, which means that the relationship is only established with the mother and her mother's family. This determination provides legal certainty for children, especially in terms of identity and civil rights.The formulation of the problem in this study is "What are the Legal Considerations of the Pontianak Religious Court in Determination Number 92/Pdt.P/2023/PA.Ptk Concerning the Application for the Origin of Children and its Legal Consequences?". This study aims to obtain data and information related to the determination of the legal status of children from unregistered marriages, analyzing the legal consequences of the child's position after being granted by the Pontianak Religious Court. The method used in this study is the normative legal method. The results of the study indicate that the determination of the Pontianak Religious Court provides legal certainty for children born from unregistered marriages, who previously did not have a clear legal status. In addition, this study also revealed that there are efforts to strengthen legal protection for children born from unregistered marriages through legal birth registration in accordance with applicable laws.The implication of determining the origin of a child by the court is to provide legal certainty for the status of the child, both as a legitimate child and a biological child. This has an impact on the recognition of the child's legal relationship with his parents and access to civil rights, such as official identity and inheritance. This determination is also a legal solution for children born from unregistered marriages, ensuring legal protection even though proof of marriage cannot be submitted.  Keywords: Determination of the Origin of Children, Pontianak Religious Court, Legal ConsiderationsAbstrak  Permohonan asal-usul anak dikabulkan oleh Pengadilan Agama berdasarkan Pasal 42 dan Pasal 2 ayat 1 Undang-Undang Nomor 1 Tahun 1974, yang menyatakan bahwa anak sah adalah anak yang lahir dari perkawinan yang sah menurut hukum agama. Selama pemohon dapat membuktikan adanya pernikahan yang sah, anak akan diakui sebagai anak sah dengan status hukum penuh. Namun, jika pernikahan tidak dapat dibuktikan, permohonan tetap dikabulkan, tetapi anak hanya diakui sebagai anak biologis, yang berarti hubungannya hanya terjalin dengan ibu dan keluarga ibunya. Penetapan ini memberikan kepastian hukum bagi anak, terutama dalam hal identitas dan hak-hak perdata.Rumusan masalah dalam penelitian ini adalah "Bagaimana Pertimbangan Hukum Pengadilan Agama Pontianak Pada Penetapan Nomor 92/Pdt.P/2023/PA.Ptk Tentang Permohonan Asal Usul Anak Serta Akibat Hukumnya ?". Penelitian ini bertujuan untuk mendapatkan data dan informasi terkait penetapan status hukum anak dari perkawinan siri, menganalisis akibat hukum terhadap kedudukan anak setelah dikabulkannya oleh Pengadilan Agama Pontianak. Metode yang digunakan dalam penelitian ini adalah metode hukum normatif. Hasil penelitian menunjukkan bahwa penetapan Pengadilan Agama Pontianak ini memberikan kepastian hukum bagi anak yang lahir dari perkawinan siri, yang sebelumnya tidak memiliki status hukum yang jelas. Selain itu, penelitian ini juga mengungkapkan bahwa ada upaya penguatan perlindungan hukum bagi anak-anak yang lahir dari perkawinan siri melalui pencatatan kelahiran yang sah sesuai dengan undang-undang yang berlaku.Implikasi dari penetapan asal-usul anak oleh pengadilan adalah memberikan kepastian hukum bagi status anak, baik sebagai anak sah maupun anak biologis. Hal ini berdampak pada pengakuan hubungan hukum anak dengan orang tuanya serta akses terhadap hak-hak perdata, seperti identitas resmi dan warisan. Penetapan ini juga menjadi solusi hukum bagi anak yang lahir dari perkawinan tidak tercatat, memastikan perlindungan hukum meskipun bukti pernikahan tidak dapat disampaikan.  Kata Kunci: Penetapan Asal-Usul Anak, Pengadilan Agama Pontianak, Pertimbangan Hukum